Topoi of Classical German Philosophy in Progress. A Thematic Issue Dedicated to Jakub Kloc-Konkołowicz - Adolphi, Rainer; Scaglia, Lara; Rockmore, Tom; Nowak, Ewa (ETHICS IN PROGRESS, 2022)
Preface by the Editors to the special thematic volume dedicated to the memory of Jakub Kloc-Konkołowicz.